Comparative Analysis of Thesis Similarity in the Governance Institute of Home Affairs: A Study of Praja from Batches XXVIII, XXIX, and XXX Using Turnitin Software - Hapsari, Rian Dwi (Indonesian Journal of Librarianship, 2023)
Background: Plagiarism is a significant global issue in academic papers, specifically in higher education. Despite the presence of numerous anti-plagiarism tools, such as Turnitin software, the associated subscription costs remained relatively high. Furthermore, software may not consistently deliver precise results and students exploit the vulnerabilities of students through deceptive tactics. Purpose: This study aimed to investigate the effects of Turnitin software on the assessment of similarity in theses of praja at the Governance Institute of Home Affairs (IPDN). Method: A descriptive qualitative method was used. Result: The results showed that use of Turnitin in the library reduced the level of similarity in praja theses by 39.01%, 29.63%, and 36.70% for Batches XXVIII, XXIX, and XXX, respectively. On average, praja required 7-10 check before similarity scores met the requirements. Conclusion: Use of Turnitin software at IPDN was very effective, specifically in assessing similarity in theses over the last three years. Keywords: Academic Integrity; Turnitin Use; Similarity Check; Governance Institute of Home Affairs Praja Theses